The Relationship between Peer Social Support with Assertiveness of Adolescent Victims of Bullying - Azzahra, Aurelya; Firman, Firman; Sukma, Dina; Hariko, Rezki (Universitas Negeri Padang, 2025)
Nowadays, bullying among adolescents, especially in the school environment, continues to show an increase, which has a major impact on the mental health of victims. One phenomenon that often appears in adolescent victims of bullying is low assertiveness, which is reflected in the tendency of victims to remain silent, unable to express their opinions, and not daring to defend their personal rights. One of the factors that affect assertiveness is the situation of the peer environment (peer social support). This study aims to describe the level of peer social support and assertiveness in adolescent victims of bullying, and analyze the relationship between the two. This study uses a quantitative method of correlational type. The population was 246 students of SMP Negeri 7 Padang aged 13–15 years (48.3% male and 51.7% female) who were identified as bullying victims. A sample of 152 students was taken by Stratified Random Sampling based on class strata. Data were collected using a peer social support questionnaire and a bullying victim assertiveness questionnaire, with sample items